A STUDY OF THE IMPACTS OF PERCEIVED VALUE ON USERS’WILLINGNESS TO CONTINUE PARTICIPATION BASED ON THE PERSPECTIVE OF ONLINE CAUSE-RELATED MARKETING - Zeng, Lizhou (Journal of Buddhist Education and Research (JBER), 2022)
At present, with the continuous development of the Internet, companies regard the Internet as an important approach to marketing. Online cause-related marketing activities are brand new marketing activities in which companies use their own online platforms to cooperate with charitable organizations, attracting users to continue participating. The willingness of users to continue participating is an important indicator to measure the success of marketing activities. According to previous studies on the online cause-related marketing, "Ant Forest" is considered as a relatively mature case incorporating the online cause-related marketing activities. Therefore, this thesis takes the users of "Ant Forest" as the survey samples and puts forward the research topic after discussion and analysis. This thesis uses literature analysis to divide perceived value into four dimensions including perceived entertainment, perceived usefulness, perceived ease of use, and social influence. Through empirical research, it is found that social influence continues to affect users. Participation willingness has a significant positive impact. Perceived usefulness has the smallest positive impact on the willingness of users to participate in the four dimensions. Based on the research results, this thesis provides some suggestions for enterprises to organize online cause-related marketing activities.